2013
DOI: 10.1105/tpc.113.111336
|View full text |Cite
|
Sign up to set email alerts
|

Structure/Function Analysis of a Type III Polyketide Synthase in the Brown Alga Ectocarpus siliculosus Reveals a Biochemical Pathway in Phlorotannin Monomer Biosynthesis

Abstract: ORCID ID: 0000-0001-7358-6282 (P.P.).Brown algal phlorotannins are structural analogs of condensed tannins in terrestrial plants and, like plant phenols, they have numerous biological functions. Despite their importance in brown algae, phlorotannin biosynthetic pathways have been poorly characterized at the molecular level. We found that a predicted type III polyketide synthase in the genome of the brown alga Ectocarpus siliculosus, PKS1, catalyzes a major step in the biosynthetic pathway of phlorotannins (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 68 publications
5
73
0
Order By: Relevance
“…Nevertheless, these short chain fatty acyl-CoA esters are unlikely to occur at the site of flavonoid biosynthesis, and the purpose of having activity with these substrates remained unknown. Recently, phloroglucinol synthase (PhlD) from Ectocarpus siliculosus (brown alga) was found to be able to synthesize phloroglucinol (32) from three units of malonyl-CoA (Scheme 10A), and a positive correlation was identified between reacclimation to seawater and the phloroglucinol content in cells [60]. The phloroglucinol synthase was also able to catalyze the decarboxylative condensation of three units of malonyl-CoA with one unit of lauroyl-CoA (n = 9) or palmitoyl-CoA (n = 13) to form tetraketide α-pyrones 33 and acylphloroglucinols 34 (Scheme 10B).…”
Section: Acridone Synthase and Quinolone Synthasementioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, these short chain fatty acyl-CoA esters are unlikely to occur at the site of flavonoid biosynthesis, and the purpose of having activity with these substrates remained unknown. Recently, phloroglucinol synthase (PhlD) from Ectocarpus siliculosus (brown alga) was found to be able to synthesize phloroglucinol (32) from three units of malonyl-CoA (Scheme 10A), and a positive correlation was identified between reacclimation to seawater and the phloroglucinol content in cells [60]. The phloroglucinol synthase was also able to catalyze the decarboxylative condensation of three units of malonyl-CoA with one unit of lauroyl-CoA (n = 9) or palmitoyl-CoA (n = 13) to form tetraketide α-pyrones 33 and acylphloroglucinols 34 (Scheme 10B).…”
Section: Acridone Synthase and Quinolone Synthasementioning
confidence: 99%
“…PhlD was co-crystallized with arachidonic acid and the structure of the enzyme was solved at 2.85 Å resolution using molecular replacement (PDB ID: 4B0N). The structure showed that an acyl-binding tunnel is present instead of a coumaroyl-binding pocket, hence enabling the PKS to accommodate longchain acyl-CoAs (Figure 10) [60]. The residues in the acyl-binding tunnel are not conserved in M. sativa CHS; when arachidonic acid is superimposed on CHS, clashes between the residues lining the site and substrate were observed (Figure 10, indicated by purple bonds of the residues).…”
Section: Acridone Synthase and Quinolone Synthasementioning
confidence: 99%
See 1 more Smart Citation
“…Particularly high tolerance ranges were observed with respect to salinity: while most Ectocarpus isolates are marine, at least one strain was isolated from a true freshwater habitat at Hopkins River Falls, Australia (West and Kraft, 1996). This freshwater strain (strain 371) is able to grow in both freshwater and seawater, adjusting its metabolism and cell wall structure to the corresponding conditions (Dittami et al, 2012;Meslet-Cladière et al, 2013;Torode et al, 2015). In addition, Ectocarpus strains related to the freshwater strain based on their internal transcribed spacer sequences, have been found in other 'extreme' environments, such as on driftwood, or in areas of highly variable temperature (Bolton, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, marine microorganisms seem extremely productive of secondary metabolites: in addition to antimicrobial metabolites, they have been found to produce antitumor, anticancer, cytotoxic, and photoprotective compounds (Bhatnagar and Kim 2010). For example, it has recently been shown that phloroglucinol, a precursor of brown algal phlorotannins used in medicine to treat abdominal pain (Chassany et al 2007), is synthesized by a polyketide synthase acquired through horizontal gene transfer (HGT) from an ancestral actinobacterium (Meslet-Cladiere et al 2013). This highlights the importance of bacterial epibionts both in algal evolution and as a source of interesting bioactive compounds (Meslet-Cladiere et al, 2013).…”
Section: Medical and Pharmaceutical Applicationsmentioning
confidence: 99%